EFFECTS OF DIETARY 17 -METHYL TESTOSTERONE ON SEX REVERSAL AND GROWTH PERFORMANCE OF AFRICAN MUD CATFISH (Clarias gariepinus) - Enuekwe, R.C; Okonji, V.A. (Nigerian Journal of Fisheries, 2019)
The search for faster growing fish with higher weight at harvest and higher yield is crucial to profitable fish culture. Male fishes are known to grow bigger than female fishes of same age. This study determined the effects of 17alpha-methyltestosterone (MT), an androgen on the sex reversal and growth performance of the African mudcatfish (Clarias gariepinus). The research was conducted at the faculty of Agriculture laboratory and the experimental fish tanks of Department of Aquaculture and Fisheries management, University of Benin, Edo Nigeria. The hormone 17 alpha – methyl testosterone was administered orally at constant rates of 30 mg/kg of feed and 60 mg/kg of feed for two time durations (28 and 35 days respectively) The MT treated fish were transferred outdoor and cultured for another 24 weeks where the effect of MT on percentage male to female, weight gain, survival rate, absolute specific and relative growth rate and net production were recorded. The fishes were evaluated to determine their sex by physical observation of the genital papilla. Data collected for the fish growth performance were analyzed and subjected to analysis of variance and significant means were separated using Duncan Multiple Range Test (DMRT). All treatment groups that received androgen 17 alpha methyltestosterone (MT) showed sex reversal in C. gariepinus with significantly (P<0.05) higher male population than female population. There was also significant difference (P<0.05) in growth performance in terms of weight gain compared with the control. The 60 mg (35 days) treatment resulted in 80.86 % male populations. 17-alpha methyltestosterone (MT) treatment of C. gariepinus resulted in mean yield of 3950 g /m2 /180 days culture period and 4226 g /m2 /180 days culture period respectively for treatment duration of 28 and 35 days of 30 mg dose while 60 mg dose for respective 28 and 35 days treatment duration gave 4474 g, 5531 g as against 3295 g /2m /180 days culture period recorded from the control group. Thus, higher fish yield was recorded for higher MT dosage and higher duration of application.